Analisis Efektivitas Alat Penukar Kalor Pelat Datar UFX-42H Terhadap Kebocoran Pelat Dalam Proses Elusi Emas - Annisa Sekarayu Permanajati; La Ode M. Firman (Fakultas Teknik Universitas Pancasila, 2021)
Heat exchanger is an equipment designed to exchange heat between two fluids by applying heat transfer by convection and conduction without mixing the two fluids. heat exchangers are used in the gold mining industry in the gold elution process stage with the type of alat penukar kalor pelat datar(PHE) UFX-42H to reheat the eluate (water) using glycol as the heating fluid. The PHE has a leak on the back base plate. This report aims to analyze the comparison of the effectiveness and LMTD of PHE between specification data and operational data at the time of leakage. The calculation off effectiveness requires the suhue, mass flow rate, and specific heat of the fluid. The results obtained were the effectiveness of the specification data is 0.83 and the mean of operational data is 0.71. The results of LMTD specification data is 23.91 and the mean of operational data is 28.1.